Multiplier Effect Pemulihan Aset di Kejaksaan - Azrica, Hanita; Safitri, Rahmad; Riza Muarrif, Muhammad (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
This study aims to evaluate the impact of asset recovery on the Bireuen District Attorney's Office on law enforcement and corruption eradication in the Bireuen Regency Government. This research is classified as literature research with a qualitative approach. The methodology used is a normative juridical study of the Attorney General's Regulation of the Republic of Indonesia Number 7 of 2020 concerning the Second Amendment to the Attorney General's Regulation Number PER-027/A/JA/ 10/2014 concerning Guidelines for Asset Recovery. The results of the study concluded that asset recovery by the Bireuen District Attorney's Office had a significant positive impact on law enforcement and corruption eradication in Bireuen Regency. Asset recovery strengthens public trust in law enforcement agencies, increases accountability, and reduces corruption.